COVID animations – Bringing Film to Life (Poster) - Lugemwa, Abbas; Gibb, Tom; Kityo, Cissy; Ahebwa, Iqra; Ssempiri, Geofrey; Nakisekka, Mariam; Mugerwa, Henry (My University, 2023)
At the pick of COVID 19 pandemic there was limited scientific information reaching the political and technical teams for timely and evidence-based information sharing with the general population. Restrictions aimed at slowing the spread of coronavirus along with disinformation, affected pandemic control measures and general health care delivery. It threatened to undermine public health targets and achievements built up over many years in areas such as Prevention of Mother to Child Transmission of HIV/AIDS, Tuberculosis, Childhood Vaccination and Maternal and Child Healthcare. We adopted a collaborative approach to confront this, building on existing relationships and previous collaborations between diverse disciplines and institutions. This involved researchers, community organisers, community leaders, frontline healthcare providers and health communicators and journalists. The aim was to provide core and relevant information to help communities to improve outcomes from the COVID 19 pandemic, including shielding the elderly and vulnerable and vaccination; to inform about the interaction between COVID and other conditions.